2020
DOI: 10.1002/bit.27368
|View full text |Cite
|
Sign up to set email alerts
|

Developing a base‐editing system to expand the carbon source utilization spectra of Shewanella oneidensis MR‐1 for enhanced pollutant degradation

Abstract: Shewanella oneidensis MR‐1, a model strain of exoelectrogenic bacteria (EEB), plays a key role in environmental bioremediation and bioelectrochemical systems because of its unique respiration capacity. However, only a narrow range of substrates can be utilized by S. oneidensis MR‐1 as carbon sources, resulting in its limited applications. In this study, a rapid, highly efficient, and easily manipulated base‐editing system pCBEso was developed by fusing a Cas9 nickase (Cas9n (D10A)) with the cytidine deaminase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 50 publications
0
25
1
Order By: Relevance
“…Although the diversity of carbon source utilization in Shewanella is limited, the metabolic machinery for the catalysis of the other carbohydrates could not be fully elucidated in S. algae 2NE11. It has already been confirmed that several strains of Shewanella can improve the decolorization efficiency when grown under additives such as carbohydrates [10] . S. algae 2NE11 seems to have the complete genomic machinery necessary to metabolize lactate and N-acetylglucosamine, which has been related to the results obtained by physiological tests.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although the diversity of carbon source utilization in Shewanella is limited, the metabolic machinery for the catalysis of the other carbohydrates could not be fully elucidated in S. algae 2NE11. It has already been confirmed that several strains of Shewanella can improve the decolorization efficiency when grown under additives such as carbohydrates [10] . S. algae 2NE11 seems to have the complete genomic machinery necessary to metabolize lactate and N-acetylglucosamine, which has been related to the results obtained by physiological tests.…”
Section: Discussionmentioning
confidence: 90%
“…S. algae 2NE11 seems to have the complete genomic machinery necessary to metabolize lactate and N-acetylglucosamine, which has been related to the results obtained by physiological tests. Previous studies indicate that they are promoters of the decolorization efficiently, for which we highlight that these two sugars could be used to optimize the decolorization process on a larger scale with strain 2NE11 [ 10 , 55 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By fusing Cas9 nickase (Cas9n (D10A)) with cytidine deaminase (rAPOBEC1), Cheng et al successfully developed the pCBEso system in S. oneidensis , whose double-locus simultaneous editing efficiency reached up to 87.5%. Compared with others, this system did not require double-strand break or repair templates and was successfully used for broadening carbon source utilization spectra for S. oneidensis ( Cheng L et al, 2020 ). The developed CRISPR-ddAsCpf1 system achieved 100% gene repression reported by green fluorescent protein (GFP).…”
Section: Combined Synthetic Biotechnology With Electrochemistry For Carbon Neutralitymentioning
confidence: 99%
“…[ 15b,17 ] Taking pCBEso system as an example, it requires that the Cs to be edited locate in the range of −18 to −13 upstream from PAM sequence. [ 12 ] These features of the base editing technologies confined the editable scope of genes in the genome, which further hindered their practical applications in editing EAMs and other microorganisms.…”
Section: Introductionmentioning
confidence: 99%